WARNA LOKAL NASKAH DRAMA “ARUK GUGAT” DAN KELAYAKANNYA SEBAGAI BAHAN AJAR SASTRA - Silvia Damayanti; Muhammad Fuad; Kahfie Nazaruddin (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problems in this research are how the local colour in drama script "Aruk Gugat" by Iswadi Pratama and the elegibility as a literature teaching material in senior high school. This research aims to describe of local colour in drama script "Aruk Gugat" by Iswadi Pratama and to determine the elegibility as an Indonesian literature teaching material in senior high school. Research method that used in this research is descriptive qualitative. The technique of collecting and data analysis in this research are technique data analysis.The results of this research describe eight Lampung local colour aspect in the drama script, namely language usage (word and expression), mores, behaviour, way of thinking, people artistry, environment, house architecture, and living and equipments live. The local colour aspect run better through by interaction of all figure. By eight local colour aspect in the script, can be seen the description of attitude to life of society which mirror in Piil Pesenggiri. The life philosophy reflection can be seen in behaviour and way of thinking of all figure in drama script. Drama script "Aruk Gugat" by Iswadi Pratama included in drama of realist comedy because in it serves the humorous conduct of all figures that depicted in behaviour, way of thinking, and Ianguage style of all figures.Based on the observation from curriculum, art aspect, and assess the liberal education and character, drama script "Aruk Gugat" by Iswadi Pratama competent to be an Indonesian literature teaching material in senior high school. Keywords: drama script, elegibility, literature teaching material